Unemployment Rate and Investment - Miroslav Kmeťko (Societas et Iurisprudentia, 2017)
Unemployment rate is really very important for financial markets. Its measure can lead to changes of basic interest rates of the Central Bank. Unemployment rate is also very close associated with the measure of firms’ investment. It represents the major signal of possible changes in basic interest rates by the Central Bank. The presented paper offers partial results of research project realised within the above-mentioned area.